Reduced Environmental Stimulation in Anorexia Nervosa: An Early-Phase Clinical Trial - Khalsa, Sahib S.; Moseman, Scott E.; Yeh, Hung-Wen; Upshaw, Valerie; Persac, Beth; Breese, Eric; Lapidus, Rachel C.; Chappelle, Sheridan; Paulus, Martin P.; Feinstein, Justin S. (Frontiers in Psychology, 2020)
Reduced Environmental Stimulation Therapy (REST) alters the balance of sensory input to the nervous system by systematically attenuating sensory signals from visual, auditory, thermal, tactile, vestibular, and proprioceptive channels. Previous research from our group has shown that REST via floatation acutely reduces anxiety and blood pressure while simultaneously heightening interoceptive awareness in clinically anxious populations. Anorexia nervosa (AN) is an eating disorder characterized by elevated anxiety, distorted body representation, and abnormal interoception, raising the question of whether REST might positively impact these symptoms. However, this approach has never been studied in eating disorders and it is unknown whether exposure to REST might worsen AN symptoms. To examine these possibilities we conducted an open-label study to investigate the safety and tolerability of REST in AN. We also explored the impact of REST on affective symptoms, body image disturbance, and interoception. Twenty-one partially weight-restored AN outpatients completed a protocol involving four sequential sessions of REST: reclining in a zero-gravity chair, floating in an open pool, and two sessions of floating in an enclosed pool. All sessions were 90 minutes, approximately one week apart. We measured orthostatic blood pressure before and immediately after each session (primary outcome), in addition to collecting blood pressure readings every 10 minutes during the session using a wireless waterproof system as a secondary outcome measure. Each participant's affective state, awareness of interoceptive sensations, and body image was assessed before and after every session (exploratory outcomes). There was no evidence of orthostatic hypotension following floating, and no adverse events (primary outcome). Secondary analyses revealed that REST induced statistically significant reductions in blood pressure, anxiety and negative affect, heightened awareness of cardiorespiratory but not gastrointestinal sensations, and reduced body image dissatisfaction. The findings from this initial trial suggest that individuals with AN can safely tolerate the physical effects of REST via floatation. Future randomized controlled trials will need to investigate whether these initial observations of improved anxiety, interoception, and body image disturbance can be effectively extended to acutely ill AN populations.